Management of Brachial Artery Pseudoaneurysms in Intravenous Drug Abusers - Ilyas Sadiq, Muhammad Nasir, Farhan Iftikhar, Rimal Ilyas, Eiman Ilyas, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the outcomes of ligation and excision of brachial artery pseudoaneurysm without revascularization in IV drugs users. Place & duration of study: From Jan 2021 to Jan 2022 at the department of Surgery of Doctors Hospital & Medical Centre Lahore. Methodology: A retrospective observational study was conducted at the surgery department of Doctors Hospital & Medical Centre Lahore for 1 year. Intravenous drug abusers, aged between 18-65 years diagnosed with brachial artery pseudoaneurysm were included in the study whereas pseudoaneurysm was caused due to arteriovenous fistula, hemodialysis, and trauma or in patients who had undergone revascularization were excluded from the study. The data were processed using SPSS 20.0. Results: A total of 15 intravenous drug users were enrolled in the study. The mean age of the participants was 33.4±5.4 years, and the mean period of addiction was 1.9±2.5 years. Majority of patients (65%) presented with an affected right arm. The most common presentations were: bleeding pseudoaneurysm (73.3%), oozing pulsatile mass (20%), and infected pulsatile mass (6.6%). Following the intervention, limb salvage was achieved in all patients. Ischemia was reported in none of the patients. Conclusion: The excision and ligation of the pseudoaneurysm can be an effective treatment option for the pseudoaneurysm of a brachial artery caused due to drug addiction.